Targeting receptor tyrosine kinase signaling: Avenues in the management of cutaneous squamous cell carcinoma - Mohan Shankar Gopinatha Pillai; Sreekumar U. Aiswarya; Chenicheri K. Keerthana; Tennyson P. Rayginia; Ruby John Anto (iScience, 2023)
Summary: Non-melanoma skin cancer (NMSC) is the most frequently diagnosed cancer worldwide. Among the various types of NMSCs, cutaneous squamous cell carcinoma (cSCC) exhibits more aggressive phenotype and is also the second-most prevalent type. Receptor tyrosine kinases (RTK) triggers key signaling events that play critical roles in the development of various cancers including cSCC. Unsurprisingly, for this reason, this family of proteins has become the cynosure of anti-cancer drug discovery pipelines and is also being considered as attractive targets against cSCC. Though inhibition of RTKs in cSCC has yielded favourable results, there is still scope for bettering the therapeutic outcome. In this review, we discuss the relevance of RTK signaling in the progression of cutaneous squamous cell carcinoma, and observations from clinical trials that used RTK inhibitors against cSCC. Backed by results from preclinical studies, including those from our lab, we also give insights into the scope of using some natural products as effective suppressors of RTK signaling and skin carcinogenesis.